The Limits of Civil Society in Democratizing the State: The Malaysian Case - Azeem Fazwan Ahmad Farouk, (Kajian Malaysia, 2011)
A vibrant and active civil society is often said to be a necessary but not sufficient condition for the consolidation of democracy. It is well known that civil society in the Western context, at least from the libertarian perspective, was born out of a struggle between the bourgeois and the feudal lord. Hegel, for example, posited that individuals in civil society would pursue their self-interest within the framework of mutually recognised rights and obligations regulated by public authority. However, the liberal perspective on civil society argues that civil society must be freed from the clutches of the state if it is to be a potent force for democratisation. Here, we argue that the emergence of civil society in a post-colonial and multi-ethnic society is highly dependent on the state and that civil society in a multi-ethnic society can also act as a polarising force.